Tumor-associated bacteria activate PRDX1-driven glycolysis to promote immune evasion and PD-1 antibody resistance in hepatocellular carcinoma - Zhang, Heng; Lan, Xi; Cai, Liquan; Gao, Xunfeng; Gao, Feng; Yu, Dan; Zhang, Jinlong; Zhang, Jinhui; Tai, Qinwen (Frontiers in Microbiology, 2025)
BackgroundRecent studies have highlighted the presence of intratumoral bacteria in hepatocellular carcinoma (HCC), yet their contribution to immunotherapy resistance remains largely unexplored. This study investigates the mechanisms by which bacterial infection reshapes tumor metabolism to undermine the efficacy of anti-PD-1 therapy.MethodsWe conducted 16S rRNA gene sequencing on 29 HCC clinical samples and integrated the data with single-cell RNA sequencing of 12,487 cells to map microbial, metabolic, and immune interactions within the tumor microenvironment. Functional validation was performed using orthotopic HCC mouse models (n = 8 per group), coupled with flow cytometry-based immune profiling.ResultsEnrichment of Streptococcaceae was strongly associated with upregulation of key glycolytic enzymes (LDHA, PKM2; p < 0.001) and dysfunction of natural killer cells (reduced CD56dim/CD16bright populations; hazard ratio = 2.15, 95% CI: 1.34–3.42). Mechanistically, bacterial colonization induced peroxiredoxin 1 (PRDX1) expression via the NF-κB pathway. This led to excessive lactate production, which suppressed CD8+ T cell cytotoxicity (p = 0.003) and increased the expression of immune checkpoint molecules (TIM-3: 2.7-fold; LAG-3: 1.9-fold). In vivo, bacterial infection decreased the antitumor efficacy of PD-1 blockade by 43% (tumor volume vs. control; p = 0.008), an effect that was reversed upon PRDX1 inhibition.ConclusionOur findings identify PRDX1 as a central node in bacteria-driven metabolic reprogramming that facilitates immune evasion and resistance to PD-1 therapy in HCC. These findings provide the first evidence linking intratumoral bacteria to PD-1 resistance via redox-regulated metabolism, proposing dual targeting of PRDX1 and gut microbiota as a novel combinatorial immunotherapy strategy.